Immunostimulatory Effects of Zingiber ottensii Rhizome Extract on Mouse Lymphocytes and Peritoneal Macrophages - Baroroh, Hanif Nasiatul; Warsinah, Warsinah; Suryoputri, Masita Wulandari; Ekowati, Heny (Majalah Obat Tradisional, 2025)
Zingiber ottensii (bangle hantu) is a member of the Zingiberaceae family, known for its pharmacological effects. Several studies have demonstrated immunomodulatory potential of Zingiberaceae rhizomes, including Zingiber officinale, Zingiber zerumbet, and Zingiber cassumunar. This study aimed to evaluate the immunomodulatory effects of Z. ottensii extract on mouse peritoneal macrophages and lymphocytes. The extract was prepared using a maceration method with 96% ethanol (1:6) and the extract compound was observed by phytochemical screening with thin layer chromatography (TLC). Phagocytotic macrophage activity was quantified using a phagocytotic assay, which use mouse peritoneal macrophages. Lymphocyte proliferation was assessed with the MTT assay and absorbance measured at 595 nm. TLC results, showed that Z. ottensii extract tested positive for flavonoids and terpenoids. The Z. ottensii extract stimulated macrophage phagocytosis activity, significantly increasing the phagocytotic index at 25 and 50 µg/mL concentrations compared to the control. Additionally, significant lymphocyte proliferation was observed with the treatment of the extract. The Z. ottensii extract may be developed for adjuvant therapy to enhance the immune responses, offering a promising natural approach to immunomodulation.